Next-generation sequencing yields the complete mitogenome of wattled crane (Bugeranus carunculatus) - Rong Hua; Duoying Cui; Jia Liu; Yuyan You; Ting Jia (Mitochondrial DNA. Part B. Resources, 2018)
In this study, the complete mitogenome sequence of wattled crane (Bugeranus carunculatus) has been decoded by next-generation sequencing and genome assembly. The assembled mitogenome, consisting of 16,679 bp, has unique 14 protein-coding genes (PCGs), 22 transfer RNAs and 2 ribosomal RNAs genes. The complete mitogenome provides essential and important DNA molecular data for further phylogenetic and evolutionary analysis for wattled crane phylogeny.